Organizational Readiness Tools for Global Health Intervention: A Review - Dearing, James W. (Frontiers in Public Health, 2018)
The ability of non-governmental organizations, government agencies, and corporations to deliver and support the availability and use of interventions for improved global public health depends on their readiness to do so. Yet readiness has proven to be a rather fluid concept in global public health, perhaps due to its multidimensional nature and because scholars and practitioners have applied the concept at different levels such as the individual, organization, and community. This review concerns 30 publically available tools created for the purpose of organizational readiness assessment in order to carry out global public health objectives. Results suggest that these tools assess organizational capacity in the absence of measuring organizational motivation, thus overlooking a key aspect of organizational readiness. Moreover, the tools reviewed are mostly untested by their developers to establish whether the tools do, in fact, measure capacity. These results suggest opportunities for implementation science researchers.